The Role of the Public in Preventing and Combating Crime - Hassan Basheet Khuwain Al-Fawadi (Journal of Madenat Alelem University College, 2024)
The responsibility of building a society in which security, stability and prosperity prevail is no longer limited to the executive state institutions alone. Rather, the citizen must have a role in confronting all the dangers that threaten the entity of that society, including crime, as it constitutes a danger to all members of society. The individual is harmed by crime, directly or indirectly, and that is why most legislation is keen to urge the citizen to contribute to fighting crime through the included provision that encourages the individual to do these actions and in some cases these provisions are mandatory that imposes a penalty on those who fail to do it. Among the actions that citizens can do is report crimes, as well as arrest their perpetrators. Given the importance of this topic, it has been highlighted in order to know whether the citizen’s contributions in this field are at the required level or not. In order to reach the necessary recommendations and proposals that increase the effectiveness of these contributions.